Fotógrafos en la prensa aragonesa - Romero Santamaría, Alfredo (Artigrama, 2012)
Resumen Ante la falta de investigaciones sobre la fotografía en Aragón, entendemos que se precisan de estímulos y ayudas para acometerlas. Con este propósito se presenta un modelo metodológico de investigación, basado en la experiencia, a través de los datos y documentos gráficos que aporta la fotografía de prensa, e incluye una extensa compilación de noticias sobre el periodismo gráfico y los fotógrafos en Aragón, a modo de cartografía, que pretende servir de atractiva y útil guía para nuevos estudios. Abstract Given the lack of research work on photography in Aragón, we believe that support and stimuli are needed in order to encourage such research. With this purpose in mind, an experience-based methodological model of research is presented, which draws on the data and graphic documents provided by press photography and includes an extensive compilation of news on graphic journalism and photographers in Aragón, with a cartographic approach, aiming to be an attractive, useful guide for further research. Key words Press photo, Aragon.